Expression profile of β-defensin genes and the effect of stocking density on them in Chinese alligator blood - LU Yao; FANG Shengguo (浙江大学学报. 农业与生命科学版)
In order to investigate the expression profile of β-defensin genes in the blood of Chinese alligator and the effect of stocking density on them, reverse transcription quantitative polymerase chain reaction (RT-qPCR) was used to detect the expression levels of β-defensin genes in blood samples from 41 seven-year-old Chinese alligators and study the defensin gene expression level differences between sexes and populations with different stocking densities. The results showed that only the AsBD5 and AsBD8 genes expressed in the blood of Chinese alligator, and there was a significantly positive correlation between their expression levels. There was no significant sex-biased difference of the defensin gene expression levels. However, their expression levels were significantly different between the two populations with different stocking densities. The defensin gene expression levels were significantly higher in the Chinese alligator population with higher stocking density, which indicating that the stocking density has some effect on the immune status of the captive Chinese alligator.